Fluorescence detection of single lithium atoms in an optical lattice using Doppler-cooling beams. (6th July 2018) - Han, Hyok Sang; Lee, Hyun Gyung; Yoon, Seokchan; Cho, D
Abstract: We demonstrate in situ fluorescence detection of 7 Li atoms in a 1D optical lattice with single atom precision. Even though illuminated lithium atoms tend to boil out, when the lattice is deep, red-detuned probe beams without extra cooling retain the atoms while producing sufficient fluorescent photons for detection. When the depth of the potential well at an antinode is 1.6 mK, an atom remains trapped for longer than 20 s while scattering probe photons at the rate of 5.3 × 10 4 s −1 . We propose a simple model that describes the dependence of the lifetime of an atom on well depth. When the number of trapped atoms is reduced, a clear stepwise change in integrated fluorescence is observed, indicating the detection of a single atom. The presence or absence of an atom is determined within 300 ms with an error of less than 5 × 10 −4 at a photon-collecting efficiency of 1%, which is limited by the small numerical aperture.